Comparative assessment of advanced power generation and carbon sequestration plants on offshore petroleum platforms. (15th July 2020) - Nascimento Silva, Fernanda Cristina; Alkmin Freire, Ronaldo Lucas; Flórez-Orrego, Daniel; de Oliveira Junior, Silvio
Abstract: On conventional offshore petroleum platforms, the combined heat and power production (CHP) currently depends on simple cycle gas turbine systems (SCGT) that operate at lower efficiency and increased environmental impact compared to modern onshore thermoelectric plants. Additionally, the reduced space and the limited weight budget on offshore platforms have discouraged operators from integrating more efficient, but also bulkier cogeneration cycles (e.g. combined cycles). In spite of these circumstances, more stringent environmental regulations of offshore oil and gas activities have progressively led to a renewed interest in the integration of advanced cogeneration systems, together with either customary or unconventional carbon capture approaches, to maintain both higher power generation efficiencies and reduced CO2 emissions. Thus, in this paper, it is evidenced how advanced gas turbine concepts are promising technologies for maintaining or even increasing efficiency, while facilitating the capture rate of CO2 produced, either for geological storage or enhanced oil recovery. Despite the profuse research works on onshore applications, advanced cogeneration and carbon capture systems have been barely studied in the context of supplying power to offshore petroleum platforms. Accordingly, the performance of a conventional offshore petroleum production platform (without carbon capture system) is compared to other configurations, based on either an amine-based chemical absorption system or oxyfuel combustion concepts ( S-Graz and Allam cycles) for CO2 capture purposes. Since the original power and heat requirements of the processing platform must remain satisfied, an energy integration analysis is performed to determine the waste heat recovery opportunities. Additionally, the exergy method helps quantifying the most critical components that lead to the largest irreversibility and identifying the thermodynamic potential for enhanced cogeneration plants. As a result, oxyfuel equipped platforms provide a diversified set of advantages, while keeping competitive efficiencies. For instance, advanced systems allow for cutting down ostensibly the atmospheric CO2 emissions compared to the conventional and amine-based power plant configurations of the FPSO. Highlights: The Allam configuration has a power efficiency of 42.63%, followed by the S-Graz with 27.10%. S-Graz-cycle powered configuration presents the best CO2 mitigation potential with only 0.014 kgCO 2 /toil . Despite oxyfuel cycles' good performance, conventional configuration still upholds the highest separation efficiency. CO2 emissions costs for oil and gas increase by nearly two to tenfold for the conventional configuration. The amine-based configuration has the largest fuel consumption and exergy destruction rate among all the four utility plants.